Systematic in vitro and in vivo characterization of Leukemia‐inhibiting factor‐ and Fibroblast growth factor‐derived porcine induced pluripotent stem cells. Issue 3 (24th March 2017) - Secher, Jan O.; Ceylan, Ahmet; Mazzoni, Gianluca; Mashayekhi, Kaveh; Li, Tong; Muenthaisong, Suchitra; Nielsen, Troels T.; Li, Dong; Li, Shengting; Petkov, Stoyan; Cirera, Susanna; Luo, Yonglun; et al.
SUMMARY: Derivation and stable maintenance of porcine induced pluripotent stem cells (piPSCs) is challenging. We herein systematically analyzed two piPSC lines, derived by lentiviral transduction and cultured under either leukemia inhibitory factor (LIF) or fibroblast growth factor (FGF) conditions, to shed more light on the underlying biological mechanisms of porcine pluripotency. LIF‐derived piPSCs were more successful than their FGF‐derived counterparts in the generation of in vitro chimeras and in teratoma formation. When LIF piPSCs chimeras were transferred into surrogate sows and allowed to develop, only their prescence within the embryonic membranes could be detected. Whole‐transcriptome analysis of the piPSCs and porcine neonatal fibroblasts showed that they clustered together, but apart from the two pluripotent cell populations of early porcine embryos, indicating incomplete reprogramming. Indeed, bioinformatic analysis of the pluripotency‐related gene network of the LIF‐ versus FGF‐derived piPSCs revealed that ZFP42 ( REX1 ) expression was absent in both piPSC‐like cells, whereas it was expressed in the porcine inner cell mass at Day 7/8. A second striking difference was the expression of ATOH1 in piPSC‐like cells, which was absent in the inner cell mass. Moreover, our gene expression analyses plus correlation analyses of known pluripotency genes identified unique relationships between pluripotency genes in the inner cell mass, which are to some extent, in the piPSC‐like cells. This deficiency in downstream gene activation and divergent gene expression may be underlie the inability to derive germ line‐transmitting piPSCs, and provides unique insight into which genes are necessary to achieve fully reprogrammed piPSCs. 84: 229–245, 2017. © 2016 Wiley Periodicals, Inc .